Language recovery in aphasia following implicit structural priming training: a case study. Issue 12 (2nd December 2017) - Lee, Jiyeon; Man, Grace
ABSTRACT: Background : Individuals with aphasia show difficulty producing sentences as a result of impaired syntactic production. Studies of structural priming in healthy speakers show that long-term learning of syntactic structures can occur via experience-based implicit adaptation in the production system. Structural priming facilitates sentence production in individuals with aphasia; however, it remains unknown if structural priming can be used as a treatment paradigm targeting longer-term language recovery in aphasia. Aims : The current study examined the feasibility and efficacy of implicit structural priming treatment in an individual with agrammatic aphasia. Methods & Procedures : MJ (our participant) received a total of 12 sessions of implicit structural priming training. We measured production of trained and untrained prepositional dative (PD) sentences on daily probes, maintenance of the treatment effects at 4-weeks post-training and training-induced changes in the production of connected speech samples (Cinderella, WAB-R picture description). Outcomes & Results : MJ showed significant improvement in producing both trained and untrained PD sentences over training sessions. Importantly, these effects were maintained at a 4-week follow-up without intervention. Notable improvement was also seen in syntactic complexity of connected speech production such as increased production of lexical verbs and sentences. Conclusions : These findings suggest that it is feasible to use implicit structural priming as a treatment paradigm to target syntactic production in aphasia and that implicit structural priming may result in long-term global language recovery in agrammatic aphasia via experience-based strengthening of connections between linguistic representations.